PRAXEOLOGICAL COMPETENCE FORMATION OF FUTURE MASTERS IN DENTISTRY: CURRENT APPROACHES - Iryna Skrypnyk; Yaroslava Kulbashna; Valeriia Zakharova (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article identifies and reveals the content of current scientific approaches to the process of praxeological competence formation of future masters in dentistry. Analysis of native and foreign scientific sources, comparison of research results, discussions with teaching staff of medical universities determined the benefit of applying systemic, student-centered, activity, competence, contextual, synergistic approaches in the educational process of medical universities. The systemic scientific approach is implemented by creating a system of components with established relationships between which there is an interaction. The system of future dentists' professional training involves components of educational process that, in turn, are the subsystem of Higher Education system of Ukraine. The student-centered approach aims to implement the individual approach to each student. It allows to help each student think creative and critically. The activity approach assumes the maturity of a graduate of a medical university to manage nonstandard professional situations. This approach identifies the precise ways of certain competence formation. The competence approach ensures the implementation of skills in professional activity. The contextual approach requires creating real life environment. The last is synergetic approach that promotes self-realization and self-development of the future dentists by establishing cooperation between the participants of the educational process. The article also describes peculiarities of mentioned scientific approaches implementation into practice of medical universities' educational process. Moreover, the article proves that the combination of these scientific and methodological approaches into the complex will improve the quality and effectiveness of the process of future dentists' praxeological competence formation.